Meningkatkan Kemampuan Menentukan Nilai Tempat Bilangan Melalui Media Sempoa Bagi Anak Kesulitan Belajar Berhitung - Salimah Putriana Siregar; Martias Z (Jurnal Penelitian Pendidikan Khusus, 2021)
Therefore, researchers try to help children in determining the value of a place of a number by using abacus media. the method used in the research is Single Subject Research (SSR) with A-B-A design. data analysis techniques are by using visual analysis of graphs. Variable measurement uses a percentage of the number of instrument items. The results of data analysis and 19 observations showed that abacus media can improve children's ability to learn math in determining the value of place numbers. The improvement of this ability is evidenced by, initially, the ability of learners is measured (A1), with percentage gains of 40%, 20%, 30%, 30%, 30%. Furthermore, after researchers intervened with abacus media (B) for six meetings, it was found that the percentage obtained increased to 70%, 60%, 90%, 80%,80%, 80%. After intervention is stopped (A2) the subjects get percentages of 80%, 80%, 60%, 70%, 70%, 80%, 80%, 80%. The results of this study prove that the use of abacus media can improve the ability to determine the place value of a number.